Long-term dynamics of the food base for nekton in Pacific waters at the Kuril Islands and Kamchatka in summer - S. V. Naidenko; M. A. Shebanova; N. A. Kuznetsova; K. V. Radchenko; V. E. Metreveli (Известия ТИНРО)
Modern data on dynamics of structure and abundance of zooplankton communities in the epipelagial layer of Pacific waters at the Kuril Islands and Kamchatka are presented on the data collected in summer of 2004–2023. On the background of changing environmental conditions, the portion of small- and medium-sized zooplankton is increased recently, mainly due to increasing abundance of moderately cold-water copepod Oithona similis and hyperiid Themisto pacifica. Among the large-sized zooplankton, increasing abundance of warm-water copepod Eucalanus bungii and decreasing number of cold-water Neocalanus copepods (especially N. cristatus) is observed. Inter-annual fluctuations of the total zooplankton stock did not exceed 3 times, while the biomass of some taxonomic groups varied in 4–9 times. The total biomass of zooplankton, which forms the basis of food base for fish and squids, is assessed as (96 ± 6).106 t in the 0–50 m layer and (90 ± 6).106 t in the 50–200 m layer. In summer, nekton consumes a small part of zooplankton production in this season (1/27). The studies of fish and squids consumption of zooplankton in the North-West Pacific did not reveal its significant dependence on the changes in structure and abundance of zooplankton communities, possibly related with oceanographic regime changes.